Návrh metodiky pro zavedení ISMS - Dokoupil, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Tato diplomová práce se zabývá návrhem metodiky pro zavedení ISMS, tedy systému řízení bezpečnosti informací (Information Security Management System). V teoretické části jsou popsány základní principy a postupy při zpracování této oblasti, včetně normativních a právních – legislativních aspektů. V další části je provedena analýza současného stavu v organizaci, na jejímž základě je v praktické části vypracován samotný návrh včetně ekonomického zhodnocení projektu a přínosů případné implementace.

This master’s thesis deals with the design of methodology for implementation of ISMS (Information Security Management System). The theoretical part describes the basic principles and procedures for processing of this domain, including normative and legal - legislative aspects. The next section is an analysis of the current state of the organization. On its basis the practical part is drafted, including an economic evaluation of the project and possible benefits of implementation.
Design of Methodology for Implementation of ISMS
Keywords: ISMS; systém řízení bezpečnosti informací; analýza; riziko; PDCA; norma; ISO/IEC 27000; ISMS; information security management system; analysis; risk; PDCA; standard; ISO/IEC 27000